1982
DOI: 10.1152/jappl.1982.52.4.991
|View full text |Cite
|
Sign up to set email alerts
|

Exercise hyperventilation in patients with McArdle's disease

Abstract: This study was undertaken to determine if patients who lack muscle phosphorylase (i.e., McArdle's disease), and therefore the ability to produce lactic acid during exercise, demonstrate a normal hyperventilatory response during progressive incremental exercise. As expected these patients did not increase their blood lactate above resting levels, whereas the blood lactate levels of normal subjects increased 8- to 10-fold during maximal exercise. The venous pH of the normal subjects decreased markedly during exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0
3

Year Published

1985
1985
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(82 citation statements)
references
References 0 publications
6
73
0
3
Order By: Relevance
“…Additionally, exogenous administration of lactate does not cause appreciable dilation (247). Finally, patients with McArdle's disease (myophosphorylase deficiency) do not produce lactic acid even in response to heavy exercise (189,276,277). These patients also show a hyperdynamic circulatory response to exercise, indicating that their vasodilator responses to exercise are excessive in the absence of lactic acid production.…”
Section: Potassium and Osmolaritymentioning
confidence: 99%
“…Additionally, exogenous administration of lactate does not cause appreciable dilation (247). Finally, patients with McArdle's disease (myophosphorylase deficiency) do not produce lactic acid even in response to heavy exercise (189,276,277). These patients also show a hyperdynamic circulatory response to exercise, indicating that their vasodilator responses to exercise are excessive in the absence of lactic acid production.…”
Section: Potassium and Osmolaritymentioning
confidence: 99%
“…Entretanto, nessa intensidade não se verifica diminuição significante do pH sanguíneo 8,9 . Para eventos fisiológicos ocorridos nessa intensidade de exercício, a percentagem do consumo de oxigênio de pico verificada no LV 1 ficou levemente acima da faixa de variação do modelo hipotético proposto por Skinner & McLellan 10 .…”
Section: Resultsunclassified
“…Foram avaliadas 37 jogadoras de futebol, com média de idade de 21,5 ± 5,9 anos (14-34), peso de 57,0 ± 8,3kg (45-79), estatura de 161 ± 7cm (146-179), índice de massa corpó-rea (IMC) de 21,8 ± 2,1kg.m 2 (18,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)3). Suas característi-cas cardiovasculares em repouso estão listadas na tabela 1.…”
Section: Methodsunclassified
“…Recently, there have been several studies wherein VT is not always consistent with LT (GREEN et al, 1983;SIMoN et al, 1983;POWERS et al, 1984;GLADDEN et al, 1985), and which are negative about the cause-effect relationship between LT and VT (HAGBERG et al, 1982;HUGHES et al, 1982). Only two studies (GREEN et al, 1983;GLADDEN et al, 1985) reported a disassociation of LT and VT, using the objective method for determining both LT and VT. GREEN et al (1983) showed that VT occurred at a significantly higher work rate than LT, and GLADDEN et al (1985) showed that agreement between both was poor (r=0.29).…”
Section: Methodsmentioning
confidence: 99%